The geoelectric model (based on the 2D inversion of the results of magnetotelluric studies) along the DOBRE-3 geotraverse - Logvinov, I.M.; Gordienko, І.V.; Tarasov, V.N. (Reports of the National Academy of Sciences of Ukraine, 2018)
Based on the twodimensional inversion of magnetotelluric data, several objects with reduced resistance are located in the band of the DOBRE-3 seismic profile. According to the inversion of only the magnetovariation data, two regions with reduced resistance are located in the upper layers of the crust; they agree with the zones of reduced velocities. By the data of variations of the geomagnetic field and magnetotelluric soundings, the object with reduced resistance in the upper mantle is located at depths of 50-90 km. Spatially and in depth, this object is consistent with the zone of partial melting associated with the Ternopil activization zone.